Importance of Aberrant Right Subclavian Artery Detection During Second Trimester Ultrasound Examination in Low-Risk Population - Seker, Erdal; Sut, Hasan; Kocar, Mustafa; Umit, Coskun; Ozkavukcu, Esra; Koc, Acar (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: Aberrant right subclavian artery, which is detected in 1-1.5% of the population, is considered an anatomical variant. Aberrant right subclavian artery is usually not symptomatic, but can sometimes lead to dysphagia due to esophageal compression. On the other hand, it has been found that it has accompanied some fetal anomalies in the last two decades. Although aberrant right subclavian artery is seen at a rate of 1-1.5% in normal chromosomal fetuses, it is seen at a rate of 19-36%, especially in fetuses with Down syndrome. STUDY DESIGN: Our study was carried out in the Department of Obstetrics and Gynaecology at Ankara University Faculty of Medicine between the dates of January 2017-January 2020. Pregnant women have had their detailed ultrasonography at our clinic and who were between 18th-24th gestational weeks were included. Amniocentesis was performed on the patients who have accepted, and genetic results were followed up. The patients who did not accept were followed up until after birth, and genetic testing was requested for babies suggestive of anomaly. RESULTS: Our study included 6205 patients who underwent detailed ultrasonography in our clinic between January 2017 and June 2020. Our detailed ultrasonography application week was between 16-24 weeks. During this period, aberrant right subclavian artery was detected in 47 of our patients. The detection rate of ARSA in the normal population in our study was 0.7% (46/6205). While aberrant right subclavian artery was the only ultrasonographic finding in 28 patients, extra anomalies were observed in 18 patients. Down syndrome was detected in four fetuses, CONCLUSION: We did not find any chromosomal anomalies in any of the patients with isolated aberrant right subclavian artery. Therefore, we do not recommend invasive intervention in patients with isolated aberrant right subclavian artery. On the other hand, our study confirmed that aberrant right subclavian artery screening should be a part of a detailed fetal ultrasonographic examination. Further studies with larger patient groups are needed.